Dexter Library staff
1940..Front Row Left to Right.Mrs. Juddi Morris.Miss Lucy Parent.Miss Shirley Pedranti.Miss Gloria Silacci..Top.Mr. Marcus Gold.Miss Helen Blair.Mr. Carl Stickler.Miss Mary Ellen Dunkleberger.Mrs. Dorothy Wright.Mrs. Lee Dye.Mr